Quality of patch testing patient's own material in patients with suspected occupational skin diseases throughout Germany: Interim results of the German Social Accident Insurance (DGUV) research project FB 317b - Symanzik, Cara; Dicke, Katja; Weinert, Patricia; Weisshaar, Elke; Brans, Richard; Skudlik, Christoph; John, Swen Malte; Obermeyer, Lara (Contact dermatitis, 2024)
Background: Due to limited availability of commercial test preparations, patch testing patient's own material (POM) is of great importance to diagnose occupational allergic contact dermatitis. Objectives: To assess the quality of performance and documentation of patch testing with POM in patients with suspected occupational skin diseases (OSD) in Germany. Methods: Retrospective-prospective analysis of protocols of patch tests with POM was conducted between 2013 and 2021 in patients with suspected OSD and submitted to statutory accident insurance institutions. Assessments were done by predefined criteria. Results: Three thousand and four patch tests with POM from 460 patients were included. A full description of the POM was provided in 73.3% of all tests. The test concentration, test vehicle and pH value were documented in 74.3%, 70.5% and 42.2% of tests, for which the respective parameters were considered relevant. One hundred and sixty-one positive reactions to POM were documented. In 72%, sufficient patch testing with commercial test substances was conducted to investigate the positive reaction. In 30.4%, consecutive patch testing of all ingredients of the POM was done. Conclusions: The results not only show considerable shortcomings mainly in documentation but also to some extent performance of patch tests with POM in patients with suspected OSD in Germany.